The Marriage of Draupadī in the Hindu and Jaina Mahābhārata - Geen, Jonathan (My University, 2001)
Broadly speaking, this thesis constitutes an examination of the history and development of the great Indian epic Mahābhārata, or the Great Story of the Descendents of Bharata. More specifically, this thesis attempts to shed light upon the origin of the Jaina Mahābhārata tradition and to elucidate its interactions with the Hindu Mahābhārata tradition over approximately two millennia. The discussion of these issues is focused upon one particular episode from the epic: the Marriage of Princess Draupadī to the five sons of King Pāṇḍu (i.e. the five pāṇḍavas).
Whether the Jainas had their own ancient Mahābhārata tradition that developed independently and in parallel with the Hindu version or they simply appropriated the epic from the Hindus and self-consciously transformed it into a Jaina Mahābhārata has been a point of disagreement among scholars. It is concluded in this thesis that the Jainas did have an ancient and distinctive Mahābhārata tradition, though the tradition was rather modest and of limited importance to the early Jaina community. Over a period of approximately 1500- 2000 years, however, and under the influence of the popularity of the Hindu Mahābhārata, the Jaina Mahābhārata took on greater prominence in the Jaina community while at the same time becoming less distinctively Jaina and increasingly similar to the Hindu version.
Finally, it is argued here that one particular short tale which is to be found in the oldest extant Hindu version of the Marriage of Draupadī was in fact originally a Jaina tale that was borrowed, adapted, and inserted into the Hindu Mahābhārata at a very early period (i.e. not later than 400 CE, and possibly much earlier).
Keywords: Religion; Religion